A Study on the Reform of China’s Agricultural Administration System - Chen, Dongfang (Asian agricultural research, 2016)
After various reforms,China’s agricultural administration system has been changing functions and improving structure,and it has basically met the requirements of agricultural and rural economic development,but in some areas,it can not be adapted to modern agricultural development. Based on the analysis of the necessity of improving agricultural administration system and the problems in current agricultural administration system,this paper comes up with the viable path choice of China’s agricultural administration system reform.